Relationship between Additional Required Nursing Documentation and Patient Outcomes: A Scoping Review - Lee, Rachel Y.; Thate, Jennifer; Withall, Jennifer; Yen, Po-Yin; Cato, Kenrick; Rossetti, Sarah C. (Applied Clinical Informatics, 2025)
Although many aspects of nursing documentation are considered an essential part of clinical communication and care coordination, other types of nursing documentation have been implemented to meet compliance and secondary uses. Adding required documentation without carefully assessing its association with patient outcomes adds excessive documentation burden on nurses. There is a gap in the evidence of the association between additional required nursing documentation and improvements in patient outcomes.This study aimed to synthesize and describe the state of the evidence on the relationship between adding required electronic nursing documentation and improved patient outcomes in inpatient hospital settings.Databases were searched using relevant terms for original studies examining the effects of additional required nursing documentation. Two authors screened titles, abstracts, and full texts for eligibility criteria. PubMed, CINAHL (EBSCO), Web of Science, and Embase were searched for data from January 2011 to May 2023.A total of 47 studies were included. Of the studies reviewed, 57.4% (n = 27) focused only on process measures, primarily measuring documentation compliance, and 42.6% (n = 20) studies included patient outcome measures such as infection rates, length of stay, and falls. Of these studies 45% (n = 9) reported statistically significant relationship between required nursing documentation and improved patient outcomes. Overall quality of evidence was generally low, with 72% (n = 34) being quality improvement studies and only one study being a randomized controlled trial.The findings of this scoping review suggest an assumed, yet unverified, connection between added required nursing documentation and improved patient outcomes that is not substantiated by high-quality empirical evidence. The paucity of studies with significant findings—and the methodological weaknesses of those that report them—suggest the need for critical examination of documentation practices that are truly beneficial to patient outcomes versus those documentation practices that are excessively burdensome.
Keywords: nursing documentation; documentation burden; nursing informatics; inpatient care; electronic health records